Peningkatan Keaktifan Dan Hasil Belajar Menggunakan Model Kooperatif Tipe Jigsaw Tema 8 Sub Tema 3 Pada Siswa Kelas IV SD Muhammadiyah Kemiri - Febrianti Arum Puspita Sari; Titi Anjarini; Supriyono Supriyono (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The aim of the study was to describe the application of the jigsaw type cooperative model theme 8 sub theme 3 in fourth grade students at Muhammadiyah Kemiri Elementary School, to describe the increase in student learning activity with the jigsaw type cooperative model theme 8 sub theme 3 in fourth grade students at Muhammadiyah Kemiri Elementary School, to describe the increase in student learning outcomes with cooperative model type jigsaw theme 8 sub theme 3 in class IV SD Muhammadiyah Kemiri. Research using the type of classroom action research. The research subjects were fourth grade students at Muhammadiyah Kemiri Elementary School for the 2021/2022 academic year with a total of 25 students. This research data collection techniques in the form of observation, interviews, tests, documentation. Analysis of the data obtained is the result of observing the implementation of learning, observing students' activeness in each cycle and tests in cycle I and cycle II